THE GARCINIA CAMBOGIA IN PHYTOTREATMENT OF OBESITY:ACTIVITIES OF THE HYDROXYCITRIC ACID - Ferrara, Lydia (European Scientific Journal, ESJ, 2014)
The objective of our work has been the identification in the bark of Garcinia cambogia (GC) of the HCA that has proven effective in blocking weight increase. The Hydroxycitric Acid (HCA) is a present alimentary acid in some varieties of tropical fruits, between which the Garcinia cambogia Desr. Its effect on the organism is that one to block to the activity of ATP-citrate lyase in charge of the transformation of alimentary sugars in fat people of reservoir for the body. The hydroxycitric acid has been isolated from the dried peels of GC after shredding and Soxhlet extraction with distilled water for several hours. After repeated treatments with alcohol on the watery residual and solvent evaporation, a residual light yellow has been obtained that it has undergone to several chromatographic analysis. The use of the chromatographic methods is useful for the purposes of evaluating a drug like phytocomplex allowing to know the nature of the active principles in it contained. The characterization of the phytocomplex thus obtained allows the location of eventual sophistications or adulterations of the vegetable drugs in products trade them monocomponent even if are not known the constituent assets or the markers of the same one. Herbal medicines only composed from GC are proved to be effective in the treatment of obesity, without to introduce side effects during the period of therapy. Undesirable reactions have been found, instead, after administration of products obtained with adding to the GC of other phytocomplexes